Managing Electronic Resources through Challenging Times - Akhir, Mazmin Mat; Jalal, Hasdarinar Abdul (2017)
E-Resources have become fundamental scholarly resources for libraries due to drastic development in publishing ecosystems. Growing numbers of scholarly journals and books are made available via online platforms either by publishers or online aggregators. As expected, many academic libraries in Malaysia are migrating from developing and maintaining conventional collections to managing electronic resources, to provide better access to scholarly contents among library users. Unquestionably, excellent features of online platforms have successfully contributed towards resource optimization in higher education institutions. Moreover, these platforms are fully equipped with automatic recordings of logins, searches and full-text downloads to allow qualitative assessment of e-resources. Other plugins and applications were installed by libraries to manage remote access to e-resources that successfully lead to realization of digital library component in academic institutions. While access to scholarly contents has been improved tremendously, libraries are facing with many uncertainties in managing electronic resources. These include ownership issues, access control, access rights, licensing policies, copyright restrictions and most importantly, pricing models and schemes. Major publishers are imposing on Big deal packages that provide access to greater number of journal titles directly from publishers’ platforms. Apparently, Big deal packages have become increasingly serious problems due to its inflexibility to cater libraries in numerous scales and focuses. As library budgets have fallen relatively, libraries are facing huge challenges to maintain subscriptions to increasing subscription cost of Big deal packages. This paper aims to explore concepts of Big deal packages, issues and challenges and possible solutions for libraries during challenging financial times.